Shock propagation in a complex laminate - Wood, David C. (Cranfield University, 2014)
The shock response of a complex laminate has been investigated using a single stage gas gun, with manganin pressure gauges employed to investigate the shock profile. The complex laminate investigated was known by the acronym TWCP and is a tape wrapped carbon fibre composite with phenolic resin matrix. Carbon fibre composites are used in the aerospace industry due to their high strength to weight ratio, so understanding of different loading conditions is needed. To investigate the shock response of the TWCP, four weave orientations were studied. The orientations investigated with respect to the shock front were 0◦ (parallel to the shock front or perpendicular to the direction of travel), 25◦, 45◦ and 90◦ (perpendicular to the shock front or parallel to the direction of travel). As well as the TWCP the shock response of the matrix material, a phenolic resin Durite SC-1008 was also investigated. For the phenolic resin matrix material a non-linear Hugoniot was found in the US-up plane with the equation of US = 2.14 + 3.79up - 1.68u2 p. Such non-linear Hugoniot behaviour has been seen in other polymeric materials, e.g. PMMA. In the pressure-volume plane deviation was seen in the higher pressure data most likely due to the materials non-linear response. For the TWCP composite, linear Hugoniots were found for all four orientations with the corresponding equations shown below. • 0◦ US = 3.69 + 0.59up • 25◦ US = 3.45 + 0.73up • 45◦ US = 3.44 + 1.12up • 90◦ US = 3.96 + 0.46up The four Hugoniots are comparable in nature and it is possible to assign a single Hugoniot with the equation US = 3.56 + 0.84up through the majority of data points. The largest deviation from this “average” response was obtained from the 90◦ orientation due to the high elastic sound speed of this weave angle. Convergence was also seen between the Hugoniots in the US-up plane towards the higher up values (approximately 1 mm μs−1). In the pressure-up plane there was very little difference between all of the experimental data, meaning that for the stress in this material, orientation makes no difference.